2009
DOI: 10.3176/earth.2009.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Thallophytic algal flora from a new Silurian Lagerstätte

Abstract: Algae have always been the most diverse and numerous eukaryotic autotrophs in marine ecosystems. Both fossil and molecular data point to an early Proterozoic origin for algae. Although known for their long evolutionary history, the fossil record of algae is sparse and mainly remains of taxa with heavily calcified thalli are preserved. However, fossils of noncalcareous algae, known as extremely sporadic and occasional finds from different parts of the world, provide important insights into the palaeobiology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…As a rule, the algal fossils in Kalana are non-calcified and do not show any traces of possible carbonate skeleton (Tinn et al, 2009). Kalania pusilla occurs as black or dark brown carbonaceous compression fossils.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a rule, the algal fossils in Kalana are non-calcified and do not show any traces of possible carbonate skeleton (Tinn et al, 2009). Kalania pusilla occurs as black or dark brown carbonaceous compression fossils.…”
Section: Methodsmentioning
confidence: 99%
“…Some surfaces show graptoloid graptolites; micropaleontological samples yield low diversity scolecodont and ostracode fauna. In addition to typical normal marine nearshore sediments and fauna, a few beds show thin lamination, layers with desiccation cracks, abundant leperditiid crustaceans, and occasional eurypterid remains, suggesting short-term periods of shallow lagoonal environments (Tinn et al, 2009). …”
Section: Geological Settingmentioning
confidence: 98%
See 1 more Smart Citation
“…Discussion. -LoDuca (1990, Mierzejewski (1991) and Tinn et al (2009) fig. 16) clearly shows a bivalved imprint in black shale.…”
Section: Genera Of Uncertain Relationships and Non-graptolitic Taxamentioning
confidence: 99%
“…In addition, the genus has been reported from the Ordovician of China (Mu et al 1979;Lin 1984), and Shrock (1928) and Tinn et al (2009) reported what were regarded as possible occurrences from the Silurian of Indiana and Estonia, respectively. Here, a new occurrence of Medusaegraptus is reported from the Pridolian to middle Lochkovian Indian Point Formation in the Flatlands area of New Brunswick (Fig.…”
Section: Introductionmentioning
confidence: 99%